Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 62252 by hovea cw last updated on 18/Jun/19

∫ln(x+1)/(x^2 −x+1)  limit ={ 0>2}

ln(x+1)/(x2x+1) limit={0>2}

Commented bymaxmathsup by imad last updated on 18/Jun/19

let I =∫_0 ^2    ((ln(x+1))/(x^2 −x +1))dx    and  f(t)=∫_0 ^2   ((ln(1+tx))/(x^2 −x +1)) dx  with t≥0  we have I =f(1)       and f^′ (t)=∫_0 ^2    (x/((1+tx)(x^2 −x+1)))dx  =(1/t)∫_0 ^2  ((1+tx−1)/((1+tx)(x^2 −x+1)))dx =(1/t)∫_0 ^2   (dx/((x^2 −x+1))) −(1/t) ∫_0 ^2      (dx/((tx+1)(x^2 −x+1)))  ∫_0 ^2    (dx/(x^2 −x+1)) =∫_0 ^2   (dx/((x−(1/2))^2  +(3/4))) =_(x−(1/2)=((√3)/2)u)   (4/3)    ∫_(−(1/(√3))) ^(3/(√3))      (1/(u^2  +1)) ((√3)/2)du  =(2/(√3)) [arctn(u)]_(−(1/(√3))) ^(√3)    =(2/(√3)){ arctan((√3))+arctan((1/(√3)))}=(2/(√3))(π/2) =(π/(√3))  let decompose F(x)=(1/((tx+1)(x^2 −x +1)→(Δ<0)))  F(x) =(a/(tx+1)) +((bx+c)/(x^2 −x+1))  a =lim_(x→−(1/t))    (tx+1)F(x) =(t^2 /(t^2  +t+1)) ⇒F(x) =(t^2 /((tx+1)(t^2  +t+1))) +((bx+c)/(x^2 −x +1))  lim_(t→+∞)  xF(x) =0 =(a/t) +b ⇒a+tb =0 ⇒tb =−a ⇒b =−(a/t) =−(t/(t^2  +t+1)) ⇒  F(x) =(t^2 /((t^2 +t+1)(tx+1))) +((−(t/(t^2 +t+1))x +c)/(x^2 −x+1))  F(0)=1 =a+c ⇒c =1−a =1−(t^2 /(t^2 +t+1)) =((t+1)/(t^2 +t+1)) ⇒  F(x) =(t^2 /((t^2 +t+1)(tx+1))) −(1/(t^2 +t+1)) ((tx−t−1)/(x^2 −x+1)) ⇒  ∫_0 ^2 F(x)dx =(t^2 /(t^2 +t+1)) ∫_0 ^2   (dx/(tx+1)) −(1/(t^2  +t+1)) ∫_0 ^2    ((tx−t−1)/(x^2 −x +1))dx  ∫_0 ^2   (dx/(tx +1)) =(1/t)[ln∣tx+1∣]_0 ^2  =(1/t)ln∣2t+1∣  ∫_0 ^2  ((tx−t−1)/(x^2 −x+1))dx =(t/2)∫_0 ^2   ((2x−1+1)/(x^2 −x+1))dx −(t+1)∫_0 ^2  (dx/(x^2 −x+1))  =(t/2)[ln∣x^2 −x+1∣]_0 ^2  −(t+1)(π/(√3)) =(t/2)ln(3)−(π/(√3))(t+1) ⇒  ∫_0 ^2  F(x)dx =(t/(t^2  +t +1))ln∣2t+1∣ −(1/(t^2  +t+1)){(((ln(3))/2)−(π/(√3)))t−(π/(√3))} ⇒  f^′ (t) =(π/(t(√3))) −(1/t)∫_0 ^2 F(x)dx  =(π/(t(√3))) −((ln∣2t+1∣)/(t^(2 )   +t +1)) −((((ln(3))/2)−(π/(√3)))/(t^2  +t +1)) +(π/(t(√3)(t^2  +t +1))) ⇒  f(t) =(π/(√3))ln(t)−∫  ((ln(2t+1))/(t^2  +t +1))dt −(((ln3)/2)−(π/(√3)))∫  (dt/(t^2  +t +1)) +(π/(√3)) ∫   (dt/(t(t^2  +t +1))) +c  ...be continued...

letI=02ln(x+1)x2x+1dxandf(t)=02ln(1+tx)x2x+1dxwitht0 wehaveI=f(1)andf(t)=02x(1+tx)(x2x+1)dx =1t021+tx1(1+tx)(x2x+1)dx=1t02dx(x2x+1)1t02dx(tx+1)(x2x+1) 02dxx2x+1=02dx(x12)2+34=x12=32u4313331u2+132du =23[arctn(u)]133=23{arctan(3)+arctan(13)}=23π2=π3 letdecomposeF(x)=1(tx+1)(x2x+1)(Δ<0) F(x)=atx+1+bx+cx2x+1 a=limx1t(tx+1)F(x)=t2t2+t+1F(x)=t2(tx+1)(t2+t+1)+bx+cx2x+1 limt+xF(x)=0=at+ba+tb=0tb=ab=at=tt2+t+1 F(x)=t2(t2+t+1)(tx+1)+tt2+t+1x+cx2x+1 F(0)=1=a+cc=1a=1t2t2+t+1=t+1t2+t+1 F(x)=t2(t2+t+1)(tx+1)1t2+t+1txt1x2x+1 02F(x)dx=t2t2+t+102dxtx+11t2+t+102txt1x2x+1dx 02dxtx+1=1t[lntx+1]02=1tln2t+1 02txt1x2x+1dx=t2022x1+1x2x+1dx(t+1)02dxx2x+1 =t2[lnx2x+1]02(t+1)π3=t2ln(3)π3(t+1) 02F(x)dx=tt2+t+1ln2t+11t2+t+1{(ln(3)2π3)tπ3} f(t)=πt31t02F(x)dx =πt3ln2t+1t2+t+1ln(3)2π3t2+t+1+πt3(t2+t+1) f(t)=π3ln(t)ln(2t+1)t2+t+1dt(ln32π3)dtt2+t+1+π3dtt(t2+t+1)+c ...becontinued...

Terms of Service

Privacy Policy

Contact: info@tinkutara.com